The validation of a basic knowledge test of music for the cultural arts guidance program (PBSB) in Malaysia using The 2 Parameter Logistic (2PL) model item response theory - Mokshein Siti Eshah, Saidon Zaharul Lailiddin, Doig Brian, (Universiti Pendidikan Sultan Idris, 2016)
The validation of a basic knowledge test of music for the cultural arts guidance program (PBSB) in Malaysia using The 2 Parameter Logistic (2PL) model item response theory by Mokshein Siti Eshah, Saidon Zaharul Lailiddin, Doig Brian,